Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.4161/cc.7.10.5867
|View full text |Cite
|
Sign up to set email alerts
|

SET8 plays a role in controlling G1/S transition by blocking lysine acetylation in histone through binding to H4 N-terminal tail

Abstract: We report evidence suggesting that methyltransferase SET8 plays a novel role in regulating cell cycle by suppressing DNA replication through histone binding. First, the distribution of SET8 is strongly cell cycle-dependent. SET8 was concentrated in the nucleus during G(1) and G(2) phases, and was excluded from the nucleus during S phase. Second, at G(1)/S transition, SET8 was degraded through ubiquitination via SCF/Skp2. Third, it was evident that the SET8 binds to the H4 N-terminal tail (H4NT) and blocks the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
66
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(68 citation statements)
references
References 0 publications
2
66
0
Order By: Relevance
“…This cohort of genes includes many that are involved in regulating apoptosis, signaling pathways, translation, cell migration, chemokine signaling, and metabolism. For example, 2°effectors expressed lower levels of genes associated with the suppression of DNA replication (setd8) (32) and dampening of cellular proliferation (lrig3) (33), as is consistent with the increased magnitude of 2°effector responses. Similarly, the higher expression in 1°effectors of genes such as satb2, a negative regulator of CD127 expression (34), and pcdh10, which can potentiate apoptosis (35), also is consistent with increased numbers of 2°effectors at the site of infection.…”
Section: Discussionmentioning
confidence: 53%
“…This cohort of genes includes many that are involved in regulating apoptosis, signaling pathways, translation, cell migration, chemokine signaling, and metabolism. For example, 2°effectors expressed lower levels of genes associated with the suppression of DNA replication (setd8) (32) and dampening of cellular proliferation (lrig3) (33), as is consistent with the increased magnitude of 2°effector responses. Similarly, the higher expression in 1°effectors of genes such as satb2, a negative regulator of CD127 expression (34), and pcdh10, which can potentiate apoptosis (35), also is consistent with increased numbers of 2°effectors at the site of infection.…”
Section: Discussionmentioning
confidence: 53%
“…Consistent with this, we found that PR-Set7 is ubiquitinated by APC cdh1 during mitosis, resulting in proteolysis of PR-Set7. Interestingly, a recent study also determined that PR-Set7 ubiquitination by SCF Skp2 and subsequent degradation of PR-Set7 at G1 were associated with S-phase entry (Yin et al 2008). While the sustained decreased levels of PR-Set7 through S phase could be due to SCF Skp2 , it remains a formal possibility that other E3 ubiquitin ligases may also participate in the degradation of PR-Set7 during S-phase progression.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent studies demonstrated that PR-Set7-mediated H4K20me1 is required for chromatin compaction and transcriptional repression of specific genes, including some involved in mammalian differentiation (Biron et al 2004;Trojer et al 2007; Kalakonda et al 2008;Sims and Rice 2008). Recent studies indicate that PR-Set7 also plays an essential role in mammalian cell cycle progression (Karachentsev et al 2005;Jorgensen et al 2007;Tardat et al 2007;Houston et al 2008;Huen et al 2008;Yin et al 2008). The loss of PR-Set7 results in a G2 arrest in human cells, and PRSet7 À/À mice are embryonic-lethal, arresting at the eightcell stage (Houston et al 2008;Oda et al 2009).…”
mentioning
confidence: 99%
“…1,2 Set8 is critically involved in multiple cellular processes including transcription regulation, cell cycle, DNA repair, genome integrity and tumor metastasis. 3 The biological function of Set8 in cell cycle is largely exerted through suppressing DNA replication. 3,4 Further studies identified that Set8 could methylate non-histone proteins such as p53, Twist, Wnt-activated genes, PCNA (proliferating cell nuclear antigen), ERa (estrogen receptor) and AR (androgen receptor).…”
mentioning
confidence: 99%
“…3 The biological function of Set8 in cell cycle is largely exerted through suppressing DNA replication. 3,4 Further studies identified that Set8 could methylate non-histone proteins such as p53, Twist, Wnt-activated genes, PCNA (proliferating cell nuclear antigen), ERa (estrogen receptor) and AR (androgen receptor). 5 These results indicate that Set8 may play a key role in the development and progression of cancers.…”
mentioning
confidence: 99%